Pengaruh Sinyal Fundamental dan Informasi Komponen Arus Kas terhadap Return Saham (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2009-2011) - Ramly Ramly (-)
Failure of earnings reflects stock prices fully implies there is other information that can be used to invest. This aims to research were to investigate alternative information of non-profit (earning) in investing by examining (1) relationship between fundamental signals (accounts receivable, inventory, gross margin, sales and administrative expenses, effective tax rate, labor force and capital expenditure)and stock returns, and (2) the information of cash flow component (operating cash flows, investing cash flows and  financing cash flow)on  stock return. The research was conducted on the Indonesia Stock Exchange (IDX) using secondary data. The samples were selected using purposive sampling method consisting of 105 data observed from 2009 to 2011. The data were analyzed using multiple linear analysis. The results of the research indicate that fundamental signals such as inventory, gross margin, sales and administrative expenses and capital expenditure have a significant influence on stock returns, while the fundamental signals such as accounts receivable, effective tax rate, and labor force indicate an insignificant influence. Similarly, information of cash flow components such as operating cash flows, investing cash flows and financing cash flow indicate an insignificant influence either. Based on the results of these studies we can conclude that the fundamental signals such as inventory, gross margin, sales and administrative expenses and capital expenditure information can be used as an alternative to investing.